Highly differentiated T cells link systemic and vascular inflammation in a mouse model of recurrent psoriasis - Casciano, Fabio; Severi, Paolo; Marongiu, Laura; Caproni, Anna; Terranova, Chiara; Spitilli, Alex; Ferrari, Davide; Ruzza, Chiara; Marconi, Peggy; Rizzo, Paola; Granucci, Francesca; Secchiero, Paola; et al. (Frontiers in Immunology, 2025)
Psoriasis is a chronic inflammatory skin-disease associated with cardiovascular comorbidities. In patients, T cells with a skin-primed phenotype are expanded in peripheral blood, indicating a role for skin to blood T cell recirculation in the development of systemic comorbidities. Here, we aimed to investigate (i) the establishment of CD4+ and CD8+ T cell memory, (ii) the accumulation of activated and terminally differentiated T cells, and (iii) the potential link with vascular inflammation, in a mouse model of recurrent psoriasis. The results revealed systemic accumulation of memory T cells in the mouse model and similar results in patients with psoriatic disease. Recurrent psoriasis-like condition in mice also induced increased activation of memory T cells, augmented frequencies of CXCR3+4-1BB+ and PD-1+TIM-3+ CD4+ T cells as well as CD8+ T cells with a highly differentiated phenotype. Notably, parallel analysis in aorta samples revealed upregulation of endothelial dysfunction (Icam1, Vcam1) and vascular inflammation markers (Ccl2, Olr1), together with a trend towards increased expression of the CXCR3 ligand, Cxcl10. Importantly CXCR3+LFA-1+ CD4+ and CD8+ T cell effectors were markedly enhanced at systemic level, thus providing insights into the mechanistic link between highly differentiated T cells, endothelial dysfunction and vascular inflammation.